A rotavirus VP4 or VP7 monoreassortant panel identifies genotypes that are less susceptible to neutralization by systemic antibodies induced by vaccination or natural infection - Tomohiro Kotaki; Yuta Kanai; Kristen M. Ogden; Megumi Onishi; Kattareeya Kumthip; Pattara Khamrin; Patcharaporn Boonyos; Pornkamol Phoosangwalthong; Phakapun Singchai; Tipsuda Luechakham; Shohei Minami; Zelin Chen; et al. (mBio, 2025)
ABSTRACT Rotavirus infections remain a significant cause of morbidity and mortality in infants. The viral surface proteins VP4 and VP7 are each classified into multiple genotypes (P[1]–P[58] for VP4 and G1–G42 for VP7), which differ in their susceptibility to neutralizing antibodies; however, detailed analyses of these differences remain limited. This study investigates the susceptibility of diverse VP4 and VP7 genotypes to neutralizing antibodies induced by vaccination or natural infection. A reverse genetics system based on the human rotavirus Odelia strain (G4P[8]) was used to create monoreassortant viruses by replacing the VP4 or VP7 genes with those from clinical isolates (obtained in Thailand) or prototype strains. We generated 11 VP4 and 19 VP7 reassortants, covering 7 and 17 genotypes, respectively. Neutralization tests using the monoreassortant viruses, immune sera, and MA104 cells indicate that the VP7 genotype, rather than the VP4 genotype, primarily influences susceptibility to neutralization. Furthermore, genotypes G2, bat-like G3, G11, G12, G25, and G33 were significantly less susceptible to sera from naturally infected Thai individuals, highlighting the importance of monitoring these genotypes. To identify the protein region responsible for susceptibility to neutralization, we generated chimeric viruses by exchanging the domains of high- and low-susceptibility VP7 genotypes and found that Domain I appears to play a substantial role in determining susceptibility. Thus, we identified multiple rotavirus genotypes with reduced susceptibility to neutralization, as well as the region primarily responsible for this reduction. These findings may help to predict possible future rotavirus outbreaks in humans and facilitate the development of effective rotavirus vaccines.IMPORTANCERotavirus, the leading cause of severe acute gastroenteritis in infants, is responsible for approximately 128,500 infant deaths globally each year. The virus’s surface proteins are highly diverse, comprising approximately 100 genotypes. This diversity affects susceptibility to neutralizing antibodies and the efficacy of vaccines. Here, we found that certain genotypes are highly resistant to serum neutralizing antibodies induced by vaccination and natural infections. Furthermore, we identified a specific region in the viral outer capsid protein that plays a significant role in determining susceptibility to neutralization. These findings may be important for predicting outbreak-causing strains and for developing more effective vaccines, ultimately contributing to the prevention of future outbreaks and improving global infant health.